Tracking based Multipath Clustering in Vehicle-to-Infrastructure Channels - Gedschold, Jonas; Schneider, Christian; Kaske, Martin; Thoma, Reiner S.; Del Galdo, Giovanni; Boban, Mate; Luo, Jian (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2018)
Reliable and accurate multipath clustering results are essential to design and parameterize geometry based (stochastic) channel models proposed by organizations such as 3GPP, COST, WINNER and others. Clustering within wireless channel models assumes that multipath components a rrive/depart with similar properties in the considered parameter domains. We propose a new approach combining tracking and initialization of the classic K-Means clustering algorithm. The results show a significantly improved consistency for cluster estimation, which subsequently allows for analyzing the lifetime of these clusters. Finally, we apply the proposed approach on two urban macro channel sounding datasets and compare them to the current 3GPP standard. We found that the angular parameters are rather similar to the standard whereas the cluster delay spreads and the number of rays per cluster differ significantly.
CRIS-Team Scopus Importer:2025-11-10